Household money holdings in the euro area: An explorative investigation - Franz Seitz; Julian von Landesberger (European Central Bank (ECB), 2010)
In this paper we analyse household holdings of the broad monetary aggregate M3 in the euro area from 1991 until 2009. We develop four models, two in nominal, two in real terms, with satisfactory economic and statistical properties. The main determinants are a transactions variable, wealth considerations, opportunity costs and uncertainty. The models are robust to different estimation strategies, samples considered and a multitude of mis-specification tests. The exercise also provides insights that go beyond the portfolio allocation decision of households. According to our analysis, it is quite apparent that in equilibrium, households jointly determine consumption and broad money holdings both influenced by wealth as well as interest rates.
Keywords: E41; C23; C32; D21; 330; cointegrated VARs; households; Money demand; Geldnachfrage; Privater Haushalt; VAR-Modell; Eurozone; EU-Staaten